Synergistic antimicrobial action and potential application for fish preservation of a bacteriocin produced by Enterococcus mundtii isolated from Odontesthes platensis - Schelegueda, Laura Inés (2015)
The aims of this study were to characterize an enterococci bacteriocinogenic strain and to evaluate its antimicrobial activity regarding its potential use for fish preservation. The bacterium, isolated from Odontesthes platensis in the Patagonian region of Argentine was identified as Enterococcus mundtii by means of biochemical test and 16S rDNA gene phylogenetic analyses. Furthermore, the gene that codifies mundticin KS was detected by PCR techniques. The bacteriocin was able to inhibit Gram positive and negative bacteria. In particular at pH 5.50, it was able to control the growth of fish bacterial flora. Construction of isobolograms and value of fractional inhibitory concentrations index showed that its use together with chitosan and sodium lactate (SL) exerted a synergic action on the inhibition of Listeria innocua, Shewanella putrefaciens and the psychrophilic flora isolated from fish. The use of the mentioned mixture of antimicrobials promoted strong changes on L. innocua and S. putrefaciens cellular components as shown by differential scanning calorimetry. Results suggest that the combination of the bacteriocin with chitosan and SL would be useful to reduce the amount of antimicrobials added to foods and to prevent the growth of spoilage bacteria and pathogenic microorganisms, such as Listeria monocytogenes.